2000
DOI: 10.1039/a907058c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of the Li+HF (v=1)→LiF+H reaction

Abstract: Laboratory angular distributions (LAB ADs) have been measured for the Li ] HF (v \ 1, j \ 1) reaction in a crossed molecular beam experiment at the collision energies 0.231 eV and 0.416 eV and compared with the results of extensive quasi-classical trajectory (QCT) calculations performed on the most recent ab initio potential energy surface (PES) for this system. The calculations also include the collision energy dependence of the integral and di †erential cross sections in the range 0.025È0.5 eV (2.4È48.2 kJ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 29 publications
8
60
0
1
Order By: Relevance
“…More ICS experiments have been carried out by Lee et al 53 and by Loesch et al 47,[54][55][56] Theoretically, the steric effect has been analyzed for the case of initially ro-vibrational excited HF molecules, HF(v r = 1, j r = 1) using quantum 48 and quasi-classical approaches (QCT). 25,49,56,58 The results obtained were in good agreement with experiment. 8,50,52 Both experiments and calculations have shown that the initial vibrational excitation of HF increases the reactivity 8,[48][49][50]59 enormously, because of the late character of the reaction barrier.…”
Section: LI + Hf Chemical Reactionsupporting
confidence: 79%
See 3 more Smart Citations
“…More ICS experiments have been carried out by Lee et al 53 and by Loesch et al 47,[54][55][56] Theoretically, the steric effect has been analyzed for the case of initially ro-vibrational excited HF molecules, HF(v r = 1, j r = 1) using quantum 48 and quasi-classical approaches (QCT). 25,49,56,58 The results obtained were in good agreement with experiment. 8,50,52 Both experiments and calculations have shown that the initial vibrational excitation of HF increases the reactivity 8,[48][49][50]59 enormously, because of the late character of the reaction barrier.…”
Section: LI + Hf Chemical Reactionsupporting
confidence: 79%
“…25,49,56,58 The results obtained were in good agreement with experiment. 8,50,52 Both experiments and calculations have shown that the initial vibrational excitation of HF increases the reactivity 8,[48][49][50]59 enormously, because of the late character of the reaction barrier. This is also the reason why simulations indicate that the reaction cross section depends strongly on the rotational alignment of HF reagents in their ground v r = 0 vibrational state, because collinear collisions favor the excitation of the vibrational stretch needed to overpass the late barrier.…”
Section: LI + Hf Chemical Reactionsupporting
confidence: 79%
See 2 more Smart Citations
“…Aside from the experimental problems related to its study, there are several works on the LiϩHF collisions, [33][34][35][36][37][38] and the LiHF(A,B,BЈ←X) electronic absorption spectrum has recently been measured by Polanyi and co-workers. 26 On the theoretical side, there is an increasing number of ab initio studies to characterize the potential energy surfaces ͑PESs͒ on the ground [39][40][41][42][43] and more recently also on the excited 44,45,42 electronic states, and many theoretical studies to simulate the collision, using quantum 39,40,46 -49 as well as classical 50,37 methods on the ground electronic state. Also some theoretical studies have been devoted to the spectroscopic study of the transition state by infrared excitation on the ground electronic state.…”
Section: Introductionmentioning
confidence: 99%